Estimativa da vida útil de hambúrguer de Carpa capim por meio de análise de sobrevivência, cut-off point e espectroscopia de infravermelho próximo - Marques, Caroline (2016)
The fish consumption in Brazil is below the world average and this is due to economic, cultural factors and also to the low availability of this food. To stimulate consumption, due to the high nutritional value of this type of meat, one of the strategies is to turn the fish into a convenient product, such as hamburger. However, due to the pH close to neutrality and the high water activity, fish and fish products have a limited shelf life, depending on storage conditions. One of the questionable parameters about the stability of this product is the lipid oxidation reaction, which occurs even at low temperatures. It is known that the sensory quality of a product is critical to the consumer at the moment of acquisition and consumption. Once the sensory monitoring of the shelf life takes time and considerable investment, the Near Infrared spectroscopy (NIR) comes as a fast instrumental technique, nondestructive and recent, with the same purpose, which can access multiple parameters from the sample at the same time. Thus, the objective of this study was to estimate the shelf life of grass carp burgers through survival analysis and cut-off point, in addition to the use of NIR to build shelf life prediction models by the Partial Least Squares (PLS) method. The burger was made with grass carp fillets ground and washed (basic washing), vacuum packed and stored under refrigeration for 30 days. A sensory panel was selected and trained to evaluate rancidity in hamburger samples by means of triangular discriminative analysis, variance statistical analysis (ANOVA), F value chart and box plots. The physical-chemical evaluation of raw materials showed adequacy with current legislation for freshness (pH and total volatile bases TVB-N); presented low lipid content and high protein content. The characterization of the product verified that the burger complies with the legislation on the lipid and protein content, with a caloric value similar to the fillets. The reference analyzes for NIR pointed out that the iodine index and water activity (Aw) were not able to differentiate the burgers during storage; the Thiobarbituric Acid Reactive Substances (TBARS) and the pH presented results corroborating the changes in the burger matrix. The rancidity was observed by the trained sensory panel and also verified by TBARS analysis, where both had exponential growth, with correlation coefficients greater than 0.95. Robust models were obtained through PLS using the NIR to rancidity, TBARS and pH parameters, a result not repeated for iodine index, Aw and color. Survival analysis determined the end of shelf life of grass carp grass burger in 17 days and the cut-off point in 15 days. Both methods were effective to estimate the shelf life of the product, unlike the NIR that underestimated the end date, generating differences ranging from 56 to 76%, not efficient for this estimative, considering the values predicted by the model generated for the defect rancidity.